2020
DOI: 10.7759/cureus.10571
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Micropapillary Carcinoma: A Rare Case of Male Breast Cancer

Abstract: Invasive micropapillary carcinoma (IMPC) is a rare form of breast cancer, accounting for 3.8-5.9% of all breast cancer types. Less than 1% of all breast cancer occurs in men and there have been only nine other cases of IMPC specifically in male patients reported in the literature. This case presents a 77-year-old Caucasian man who was found to have IMPC of the left breast after presenting for a painless mass in the left lower subareolar region. After a left modified radical mastectomy, the patient was found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…While micropapillary histological architecture is found in up to 2-8% of all breast cancers, pure micropapillary carcinoma is infrequent and comprises 0.9-2% of breast carcinomas [3]. The mean age of diagnosis is 59 years, and it is predominantly found in females, with only a few case reports for male IMPC in existence [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…While micropapillary histological architecture is found in up to 2-8% of all breast cancers, pure micropapillary carcinoma is infrequent and comprises 0.9-2% of breast carcinomas [3]. The mean age of diagnosis is 59 years, and it is predominantly found in females, with only a few case reports for male IMPC in existence [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies supporting the effectiveness of the combination of adjuvant hormone therapy and chemotherapy. In surgical treatment, radical mastectomy and lymphnode dissection, which are associated with lower rates of local recurrence, are performed [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Data on molecular typing characteristics of MBMC are limited. Coyle et al reported that a patient was positive for ER and PR, but negative for HER-2 [5] ; Ishita et al also reported a patient with MBMC who was positive for ER and PR, but negative for HER-2 [16] . It was noted in this case that both ER and PR were positive.…”
Section: Discussmentioning
confidence: 99%
“…Male breast micropapillary carcinoma (MBMC) has features of early metastasis, late staging, and poor prognosis [5] . At present, there is no clear diagnosis and treatment plan for MBMC, and the existing treatment measures are mostly based on the diagnosis and treatment experience of female breast cancer, and the treatment effect is not ideal.…”
Section: Introductionmentioning
confidence: 99%